Träning av sydafrikansk pälssäl och afrikansk stäppelefant på djurpark - skillnader och likheter - Hedlund, Sandra (SLU/Dept. of Animal Environment and Health (until 231231), 2015)
Training of zoo animals started when the first zoo opened in 1752. The difference between then and now is that from the beginning the zookeepers did not focus so much on animal welfare. Nowadays animal welfare is the most important thing in the training. Therefore, the zookeepers are training the animals mainly for veterinary purposes and activation. The training makes the animals less stresses during handling.